VeggieSense: A non-taste multisensory exposure technique for increasing vegetable acceptance in young children. (1st January 2022) - Roberts, Alan Parry; Cross, Lara; Hale, Amy; Houston-Price, Carmel
Abstract: Vegetable consumption falls well below recommended levels for children in the UK. Previous research has found that repeated non-taste sensory exposure over the course of several days increases young children's willingness to touch and taste vegetables. The current study examined the impact of a one-off multisensory non-taste exposure intervention that took place on a single day on children's willingness to taste and intake of the exposed vegetables. Children ( N  = 110) aged 3- to 4-years-old were assigned to one of three intervention groups or to a control group. Children in all groups participated individually in a single activity session delivered in their nursery. Children in the intervention conditions took part in fun activities that provided either (a) visual exposure, (b) smell and visual exposure, or (c) smell, touch and visual exposure to six raw and prepared vegetables. Children in the control group engaged in a visual exposure activity with non-food items. After the exposure activities, all children were offered the prepared vegetables to eat; their willingness to taste and intake of the vegetables were measured. Results confirmed previous findings of sensory exposure activities increasing children's willingness to taste and intake of vegetables and revealed linear trends in both measures of acceptance with the number of senses engaged; children who took part in smell, touch and visual activities showed the highest level of acceptance. Findings suggest that multisensory exposures are effective in increasing consumption of vegetables in young children and that the effect of sensory exposure to healthy foods may be cumulative, with the more senses engaged prior to offering a food, the better.